Difference between revisions of "Foldl as foldr alternative"

From HaskellWiki
Jump to navigation Jump to search
m
Line 1: Line 1:
 
This page explains how <hask>foldl</hask> can be written using <hask>foldr</hask>. Yes, there is already [[Foldl as foldr|such a page]]! This one explains it differently.
 
This page explains how <hask>foldl</hask> can be written using <hask>foldr</hask>. Yes, there is already [[Foldl as foldr|such a page]]! This one explains it differently.
  +
   
 
The usual definition of <hask>foldl</hask> looks like this:
 
The usual definition of <hask>foldl</hask> looks like this:
Line 11: Line 12:
   
   
Now the <hask>f</hask> never changes in the recursion, so we don't really have to worry too much about it. For simplicity, then, let's pick one in particular:
+
Now the <hask>f</hask> never changes in the recursion. It turns out things will be simpler later if we pull it out:
   
   
 
<haskell>
 
<haskell>
f :: Ord x => Set x -> x -> Set x
+
foldl :: (a -> x -> r) -> a -> [x] -> r
f a x = insert x a
+
foldl f a list = go a list
 
where
 
go a [] = a
 
go a (x : xs) = go (f a x) xs
 
</haskell>
 
</haskell>
 
 
While we're at it, let's give a name to <hask>foldl f</hask>: <hask>stuff</hask>. So
 
 
 
<haskell>
 
stuff :: Ord x => Set x -> [x] -> Set x
 
stuff a [] = a
 
stuff a (x:xs) = stuff (f a x) xs
 
</haskell>
 
 
 
takes all the elements of the list it's given and stuffs them into the <hask>Set</hask> it's given.
 
   
   
Line 36: Line 27:
   
   
For some reason (maybe we're crazy; maybe we want to do weird things with fusion; who knows?) we want to write this using <hask>foldr</hask>. Haskell programmers like curry, so it's natural to see <hask>stuff a xs</hask> as <hask>(stuff a) xs</hask>&mdash;that is, to see <hask>stuff a</hask> as a function that takes a list and returns the result of folding <hask>f</hask> into the list starting with an accumulator value of <hask>a</hask>. This perspective, however, is the ''wrong one'' for what we're trying to do here. So let's change the order of the arguments of <hask>stuff</hask>.
+
For some reason (maybe we're crazy; maybe we want to do weird things with fusion; who knows?) we want to write this using <hask>foldr</hask>. Haskell programmers like curry, so it's natural to see <hask>go a xs</hask> as <hask>(go a) xs</hask>&mdash;that is, to see <hask>go a</hask> as a function that takes a list and returns the result of folding <hask>f</hask> into the list starting with an accumulator value of <hask>a</hask>. This perspective, however, is the ''wrong one'' for what we're trying to do here. So let's change the order of the arguments of the helper:
   
   
 
<haskell>
 
<haskell>
stuffy :: Ord x => [x] -> Set x -> Set x
+
foldl :: (a -> x -> r) -> a -> [x] -> r
stuffy [] a = a
+
foldl f a list = go2 list a
 
where
stuffy (x : xs) a = stuffy xs (f a x)
 
  +
go2 [] a = a
 
go2 (x : xs) a = go2 xs (f a x)
 
</haskell>
 
</haskell>
   
   
So now we see that <hask>stuffy xs</hask> is a function that takes an accumulator and uses it as the initial value to fold <hask>f</hask> into <hask>xs</hask>. With this shift of perspective, we can rewrite <hask>stuffy</hask> just a little:
+
So now we see that <hask>go2 xs</hask> is a function that takes an accumulator and uses it as the initial value to fold <hask>f</hask> into <hask>xs</hask>. With this shift of perspective, we can rewrite <hask>go2</hask> just a little:
   
   
 
<haskell>
 
<haskell>
stuffy :: Ord x => [x] -> Set x -> Set x
+
foldl :: (a -> x -> r) -> a -> [x] -> r
stuffy a [] = \a -> a
+
foldl f a list = go2 list a
  +
where
stuffy (x : xs) = \a -> stuffy xs (f a x)
 
 
go2 [] = \a -> a
 
go2 (x : xs) = \a -> go2 xs (f a x)
 
</haskell>
 
</haskell>
   
Line 60: Line 55:
   
 
<haskell>
 
<haskell>
 
foldl f a list = go2 list a
stuffy :: Ord x => [x] -> Set x -> Set x
 
  +
where
stuffy [] = (\a -> a)
 
stuffy (x : xs) = \a -> (stuffy xs) (f a x)
+
go2 [] = (\a -> a)
 
go2 (x : xs) = \a -> (go2 xs) (f a x)
 
</haskell>
 
</haskell>
   
   
This isn't an academic paper, so we won't mention Graham Hutton's "Tuturial on the Universality and Expressiveness of Fold", but <hask>stuffy</hask> fits the <hask>foldr</hask> pattern:
+
This isn't an academic paper, so we won't mention Graham Hutton's "Tuturial on the Universality and Expressiveness of Fold", but <hask>go2</hask> fits the <hask>foldr</hask> pattern:
   
   
 
<haskell>
 
<haskell>
stuffy :: Ord x => [x] -> Set x -> Set x
+
go2 ys = foldr whatsit (\a -> a) ys
stuffy ys = foldr whatsit (\a -> a) ys
 
 
where
 
where
 
whatsit x r = \a -> r (f a x)
 
whatsit x r = \a -> r (f a x)
Line 81: Line 76:
   
 
<haskell>
 
<haskell>
stuffy :: Ord x => [x] -> Set x -> Set x
+
foldl f a list = (foldr whatsit (\a -> a) list) a
stuffy list a = (foldr whatsit (\a -> a) list) a
 
 
where
 
where
 
whatsit x r = \a -> r (f a x)
 
whatsit x r = \a -> r (f a x)
Line 88: Line 82:
   
   
 
And that's all she wrote! One way to look at this final expression is that <hask>whatsit</hask> takes an element of the list, a function produced by folding over the rest of the list, and the value of an accumulator. It applies <hask>f</hask> to the accumulator it's given and the list element, and passes the result forward to the function it got.
And that's just about it! We wanted <hask>stuff</hask>, however, not <hask>stuffy</hask>, so let's swap the argument order again:
 
 
 
<haskell>
 
stuff :: Ord x => Set a -> [x] -> Set x
 
stuff a list = (foldr whatsit (\a -> a) list) a
 
where
 
whatsit x r = \a -> r (f a x)
 
</haskell>
 
 
 
Now since we do want to be able to use general <hask>foldl</hask> forms, we should generalize it again:
 
 
 
<haskell>
 
foldl :: (a -> x -> r) -> a -> [x] -> r
 
foldl f a xs = (foldr whosit (\a -> a) list) a
 
where
 
whosit x r = \a -> r (f a x)
 
</haskell>
 
 
 
The way to look at this final expression is that <hask>whosit</hask> takes an element of the list, a function produced by folding <hask>f</hask> into the rest of the list, and the initial value, <hask>a</hask> of an accumulator. It applies <hask>f</hask> to the accumulator it's given and the list element, and passes the result forward to the function it got.
 

Revision as of 05:42, 4 September 2014

This page explains how foldl can be written using foldr. Yes, there is already such a page! This one explains it differently.


The usual definition of foldl looks like this:


foldl :: (a -> x -> r) -> a -> [x] -> r
foldl f a [] = a
foldl f a (x : xs) = foldl f (f a x) xs


Now the f never changes in the recursion. It turns out things will be simpler later if we pull it out:


foldl :: (a -> x -> r) -> a -> [x] -> r
foldl f a list = go a list
  where
    go a [] = a
    go a (x : xs) = go (f a x) xs




For some reason (maybe we're crazy; maybe we want to do weird things with fusion; who knows?) we want to write this using foldr. Haskell programmers like curry, so it's natural to see go a xs as (go a) xs—that is, to see go a as a function that takes a list and returns the result of folding f into the list starting with an accumulator value of a. This perspective, however, is the wrong one for what we're trying to do here. So let's change the order of the arguments of the helper:


foldl :: (a -> x -> r) -> a -> [x] -> r
foldl f a list = go2 list a
  where
    go2 [] a = a
    go2 (x : xs) a = go2 xs (f a x)


So now we see that go2 xs is a function that takes an accumulator and uses it as the initial value to fold f into xs. With this shift of perspective, we can rewrite go2 just a little:


foldl :: (a -> x -> r) -> a -> [x] -> r
foldl f a list = go2 list a
  where
    go2 [] = \a -> a
    go2 (x : xs) = \a -> go2 xs (f a x)


Believe it or not, we're almost done! How is that? Let's parenthesize a bit for emphasis:


foldl f a list = go2 list a
  where
    go2 [] = (\a -> a)
    go2 (x : xs) = \a -> (go2 xs) (f a x)


This isn't an academic paper, so we won't mention Graham Hutton's "Tuturial on the Universality and Expressiveness of Fold", but go2 fits the foldr pattern:


go2 ys = foldr whatsit (\a -> a) ys
  where
    whatsit x r = \a -> r (f a x)


Substituting this in,


foldl f a list = (foldr whatsit (\a -> a) list) a
  where
    whatsit x r = \a -> r (f a x)


And that's all she wrote! One way to look at this final expression is that whatsit takes an element of the list, a function produced by folding over the rest of the list, and the value of an accumulator. It applies f to the accumulator it's given and the list element, and passes the result forward to the function it got.